Effects of pretreatments and hydrothermal aging on biaxial flexural strength of lithium di-silicate and Mg-PSZ ceramics. (December 2016) - André, Maria; Kou, Wen; Sjögren, Göran; Sundh, Anders
Abstract: Objectives: To evaluate the effect of specimen thickness, pretreatment and hydrothermal aging on the biaxial flexural strength (BFS) of lithium di-silicate glass (e.max Cad) and magnesia-stabilized zirconia (ZirMagnum) ceramic discs. Methods: The e.max Cad discs was studied: i) crystallized, ii) crystallized and glazed and iii) crystallized, glazed and unglazed side etched with hydrofluoric acid. The ZirMagnum discs were studied: i) as delivered, ii) after sandblasting and iii) after heat treatment similar to veneering. Hydrothermal aging was simulated by autoclave treatment. Results: The BFS of all the ZirMagnum specimens was superior (p < 0.001) to all the e.max Cad specimens. Glazing the 0.4 mm e.max Cad discs reduced (p < 0.05) their BFS compared with the unglazed 0.8 mm specimens, whereas glazing of 0.8 mm discs had no influence (p > 0.05) on the strength. Etching and autoclaving of e.max Cad did not affect (p > 0.05) the BFS. For ZirMagnum sandblasting with 0.2 MPa or 0.6 MPa did not influence the biaxial flexural strength (p > 0.05), whereas heat treatment reduced (p < 0.01) the BFS of 0.6 MPa sandblasted ZirMagnum. Autoclaving reduced the strength (p < 0.05) compared with ZirMagnum as delivered, whereas autoclaving of the 0.6 MPa sandblasted and heat-treated specimens did not influence (p > 0.05) the BFS. Glazing, etching and sandblasting increased (p < 0.05) surface roughness. Conclusions: The effects of glazing, heat treatment, aging and mechanical treatment of the materials evaluated should be considered since their strength could be affected. Clinical significance: Mechanical properties of restorations made from prefabricated ceramic blocks could be affected of various treatments and could change over time.